Unilateral nephrectomized SHR/NDmcr-cp rat shows a progressive decline of glomerular filtration with tubular interstitial lesions - Shinozaki, Y; Fukui, K; Maekawa, M; Toyoda, K; Yoshiuchi, H; Inagaki, K; Uno, K; Miyajima, K; Ohta, T (Physiological research, 2023)
In patients with diabetic kidney disease (DKD), the estimated glomerular filtration rate (eGFR) or creatinine clearance rate (Ccr) is always used as an index of decline in renal function. However, there are few animal models of DKD that could be used to evaluate renal function based on GFR or Ccr. For this reason, it is desirable to develop animal models to assess renal function, which could also be used for the evaluation of novel therapeutic agents for DKD. Therefore, we aimed to develop such animal model of DKD by using spontaneously hypertensive rat (SHR)/NDmcr-cp (cp/cp) rats with the characteristics of obese type 2 diabetes and metabolic syndrome. As a result, we have found that unilateral nephrectomy (UNx) caused a chronic Ccr decline, development of glomerular sclerosis, tubular lesions, and tubulointerstitial fibrosis, accompanied by renal anemia. Moreover, losartan-mixed diet suppressed the Ccr decline in UNx-performed SHR/NDmcr-cp rats (UNx-SHR/cp rats), with improvement in renal anemia and histopathological changes. These results suggest that UNx-SHR/cp rats could be used as a DKD model for evaluating the efficacy of therapeutic agents based on suppression of renal function decline.
Keywords: metabolický syndrom; Diabetes Mellitus, Type 2; Rats; Diabetic Nephropathies; Metabolic Syndrome; Animals; krysa rodu Rattus; Losartan; diabetické nefropatie; diabetes mellitus 2. typu; potkani inbrední SHR; zvířata; Rats, Inbred SHR; losartan